Post-traumatic stress disorder (PTSD) and other trauma-related mental disorders in elite athletes: a narrative review. Issue 12 (25th June 2019) - Aron, Cindy Miller; Harvey, Sydney; Hainline, Brian; Hitchcock, Mary E; Reardon, Claudia L
Abstract : This narrative review examines post-traumatic stress disorder (PTSD) and other trauma-related disorders—mental health conditions with complex diagnosis and treatment considerations—in elite athletes. Athletes may exhibit greater rates of PTSD (up to 13%–25% in some athlete populations) and other trauma-related disorders relative to the general population. We describe common inciting events leading to symptoms of PTSD in elite athletes, including trauma incurred in sports participation through direct physical injury, secondary/witnessed traumatic events, or abusive dynamics within sports teams. Symptoms of PTSD may significantly impact athletes' psychosocial and sport-related function through avoidance, hypervigilance and dissociative behaviours, which, in turn, may delay recovery from musculoskeletal injury. While PTSD may be common among elite athletes, recognition by providers who do not routinely screen for trauma-related disorders may be challenging because of the tendency of athletes to mask symptoms of PTSD and other trauma-related disorders. Early identification of athletes suffering from trauma-related symptoms, including those of acute stress disorder, may prevent progression to PTSD, while treatment of athletes already meeting criteria for PTSD may improve life functioning and sports performance outcomes. Current evidence supports increasing awareness of PTSD in athletes and use of screening tools to identify athletes who may benefit from trauma-informed medical or psychotherapeutic interventions.